EFFECT OF TRANSFORMATIONAL LEADERSHIP ON EMPLOYEE CREATIVITY: PERCEIVED ORGANIZATIONAL SUPPORT MEDIATOR (STUDY EMPIRIC AT FIVE-STAR HOTELS IN JAKARTA) - Anggiani, Sarfilianty (PEOPLE: International Journal of Social Sciences, 2019)
This study aims to examine and analyze the effect of transformational leadership mediated by perceived organizational support on employee creativity at five-star hotels in Jakarta, with questionnaires being distributed to 356 employees. Structural equation model was used to analyze the data. Based on the descriptive statistics, transformational leadership has a mean value (average) of 4.28 that means transformational leadership can influence employee perception in establishing a good and effective relationship between leaders and employees to create positive and creative attitudes as well as behavior; Perceive organizational support has a mean value (average) of 4.06 means that perceived organizational support can improve employee equality and desire to work creatively and effectively; and Employee creativity has a mean value (average) of 4.92 shows employee has a great creativity to bring new idea and creative behavior to deliver the best service quality. Based on the results of hypothesis testing, it found that there is positive effect of transformational leadership on employee creativity of 0.028 <0.05; positive effect of transformational leadership on perceived organizational support of 0.000 <0.0; positive effect of perceived organizational support on employee creativity of 0.042> 0.05; and the last hypothesis found that transformational leadership has strong effect on employee creativity mediated by perceived organizational support with statistic beta 0,868 is bigger than direct effect of transformational leadership on employee creativity with beta value 0.724. The conclusion of this study is a strong positive effect of transformational leadership on employee creativity mediated by perceived organizational support at five-star hotels in Jakarta.